2003
DOI: 10.1016/s0741-5214(03)00944-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of cine magnetic resonance angiography in quantifying aneurysm pulsatility associated with endoleak

Abstract: Cine MRA may be used to accurately quantify AAA wall motion before and after endovascular stent-graft treatment. The extent of change in diameter corresponds to the type of endoleak, with antegrade (type I) endoleak generating greater pulsatile change in diameter than retrograde-collateral (type II) endoleak or no endoleak. Cine MRA may provide a noninvasive means of assessing the success of endovascular treatment of AAA. Further studies will be necessary to confirm the utility and efficacy of cine MRA in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Several authors have since examined the movement of aortic stentgrafts and the relationship to endoleak and/or stent-graft dislocation. [2][3][4][5][6] In this case, analysis of the dynamic CTA obtained 2 years after the EVAR procedure revealed an 11% change of the right iliac limb diameter during the cardiac cycle. Moreover, we observed that the aorta and the stent-graft moved 3 mm up and down with every heartbeat.…”
Section: Discussionmentioning
confidence: 69%
“…Several authors have since examined the movement of aortic stentgrafts and the relationship to endoleak and/or stent-graft dislocation. [2][3][4][5][6] In this case, analysis of the dynamic CTA obtained 2 years after the EVAR procedure revealed an 11% change of the right iliac limb diameter during the cardiac cycle. Moreover, we observed that the aorta and the stent-graft moved 3 mm up and down with every heartbeat.…”
Section: Discussionmentioning
confidence: 69%
“…Anecdotal reports have suggested a high chance of recurrence after sealing of primary type-1a endoleaks has occurred. 5,15,16 Only one recurrence was detected after 5 years, probably caused by progression of disease. It is believed that this low recurrence rate is directly associated with the criteria for watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources include gastrointestinal filling and peristalsis 3, 4 , the cardiac cycle 5 , medication-induced changes in organ dimensions 6 , vasculopathy 7 , vascular surgery including renal vessel stenting 8 , postoperative adhesions causing organ shift, and physiologic deformation of the tumor in response to treatment. Together, these sources define the margins that during the treatment-planning process should be added to organs at risk to minimize treatment-related side effects.…”
Section: Introductionmentioning
confidence: 99%